The role of urban design in addressing the problem of urban growth and urban sustainability of the city of Baghdad (Journal of the College of Basic Education, 2022)
The basic assumptions and future expectations on which the basic design of the city of Baghdad was based and applied in the current stage, represented by Paul Service’s design, have become mostly unrealistic and inaccurate, as it is the design that the city of Baghdad still depends on in the distribution of its land uses despite the expiry of its validity period since 2000, including It is nearly 21 years old, therefore, the urban feasibility requires the implementation of a study to develop a modern planning for the city of Baghdad, its suburbs and its region, provided that this study deals with updating the concepts and foundations for the future growth of Baghdad, and working to stop the urban sprawl and the horizontal expansion of the city. Based on the foregoing, the research was divided into two chapters. The first chapter dealt with the most prominent problems of urban growth in the city of Baghdad. The first section dealt with the change of administrative boundaries as a problem of urban growth in the city of Baghdad, while the second topic dealt with the problems of urban growth in the city of Baghdad in the current stage. While the second chapter of this research is devoted to addressing a modern foundation design researched by the Lebanese company Khatib and Alami for the city of Baghdad, which is under study and prepared for implementation, as it achieves planning treatments that achieve urban sustainability for the city, as well as prominent aspirations and future visions for sustainable urban growth for the city of Baghdad, and given what it includes Among the projects that have a future role in achieving urban sustainability for the city of Baghdad, such as the development projects of Al-Rasheed camp, the Al-Sadr City 10 x 10 project, the development of the Kadhimiya area, the Basmaya residential project, the Uwairej area and Bob Al-Sham, and the research concluded with a conclusion summarizing the findings and recommendations of the research.